Treatment with soluble VEGF receptor reduces disease severity in murine collagen-induced arthritis. - Miotla, J; Maciewicz, R; Kendrew, J; Feldmann, M; Paleolog, E (2000)
Maintenance of the invasive pannus in rheumatoid arthritis is an integral part of disease progression. The synovial vasculature plays an important role in the delivery of nutrients, oxygen, and inflammatory cells to the synovium. Vascular endothelial growth factor (VEGF), an endothelial mitogen expressed by cells within the synovial membrane, is thought to contribute to the formation of synovial blood vessels. Our objective in this study was to measure the kinetics of VEGF production in a murine model of collagen-induced arthritis and to determine whether VEGF blockade reduces disease progression. Synovial cells isolated from the knee joints of naive or sham-immunized mice, or from mice immunized with collagen but without arthritis, released little or no detectable VEGF. Onset of arthritis was associated with expression of VEGF mRNA and protein. The levels of VEGF secreted by synovial cells isolated from the joints of mice with severe arthritis were significantly higher than from mice with mild disease. To block VEGF activity, animals were treated after arthritis onset with a soluble form of the Flt-1 VEGF receptor (sFlt), which was polyethylene glycol (PEG)-linked to increase its in vivo half-life. Treatment of arthritic mice with sFlt-PEG significantly reduced both clinical score and paw swelling, compared with untreated or control-treated (heat-denatured sFlt-PEG) animals. There was also significantly less joint inflammation and reduced bone and cartilage destruction in sFlt-PEG-treated animals, as assessed by histology. Our data demonstrate that, in collagen-induced arthritis, expression of the potent angiogenic cytokine VEGF correlates with disease severity. Furthermore, specific blockade of VEGF activity results in attenuation of arthritis in both macroscopic and microscopic parameters. These observations indicate that blood vessel formation is integral to the development of arthritis and that blockade of VEGF activity might be of therapeutic benefit in rheumatoid arthritis.